Re-Designing Secure Children’s Homes Through a Child-First Lens - Caroline Andow; Stefan Kleipoedszus; Rachel Dunn; Nicola Wake; Raymond Arthur; Adeela Shafi; David Gibson (Societies)
This article explores existing learning gaps concerning optimal ways to support children within and beyond secure care in England and Wales, with a specific focus on Secure Children’s Homes (SCHs). Insights from key stakeholders working in SCHs are often omitted from research despite being fundamental to understanding both challenges and best-practice initiatives. The Children’s Residential Care Research Network, which is a collaboration between the authors, aims to develop novel research with stakeholders working across the secure children’s estate and expand the extant literature to inform the design and build of future Secure Children’s Homes (SCH) through a Child-First lens. The research presented here involves a mixed-methods approach gathering rich qualitative data from participants across the sector. Fifty-three participants engaged in participatory methodologies, focus groups, and interviews, which led to a large data set. Thematic analysis identified three key themes to inform the design and build of new SCHs. SCHs should (i) be close to home to enable family involvement and continuity of care, (ii) feel like a home, and (iii) be flexible and adaptive to changing needs. These findings are feeding into the design of two new homes in England as well as the refurbishment of existing provision and can also influence future expansion of the secure estate. The research also contributes to knowledge about how the Child-First tenets can be engaged to improve outcomes for children deprived of their liberty, both in and outside the youth justice system.